Evaluating the role of digital intervention design in treatment outcomes and adherence to eTherapy programs for eating disorders: A systematic review and meta‐analysis. Issue 10 (22nd July 2019) - Barakat, Sarah; Maguire, Sarah; Smith, Kathryn E.; Mason, Tyler B.; Crosby, Ross D.; Touyz, Stephen
Abstract: Objective: Despite the existence of reviews which document the effectiveness of online therapies, there is little consensus regarding the exact components of online treatment delivery that are most effective in maintaining user engagement and reducing eating disorder (ED) symptomology. The current review and meta‐analysis aimed to determine which components of web‐based, ED self‐help interventions are associated with lower attrition and improved therapeutic outcome. Method: A systematic search of electronic databases (PsycINFO, Medline, Web of Science, Scopus) was conducted for published studies of web‐based interventions for EDs and a meta‐analysis of the final included studies was performed. Each intervention was coded across four dimensions, including the multimedia channels employed (e.g., text, audio, videos), degree of user interactivity (e.g., online self‐monitoring, skills exercises), level of automated feedback (e.g., reminders, personalized feedback), and technological device through which the program was accessed (e.g., smartphone, computer). Results: A final 23 papers were included. The results of meta‐regressions indicated that higher scores on the multimedia subscale were associated with greater ED symptom improvement in treatment groups. Conversely, a higher degree of feedback in the treatment group was associated with a group difference in ED psychopathology favoring the control group. Other intervention components were not associated with treatment outcome or dropout. Discussion: The results are discussed in relation to limitations of the scale used to quantify digital intervention features, as well as the limited diversity and technological sophistication of available ED digital interventions. Such findings indicate the importance of understanding the digital components, which differentiate online therapeutic programs. Resumen: Objetivo: A pesar de las existencia de revisiones que documentan la efectividad de las terapias en línea, hay poco consenso acerca de los componentes exactos de los tratamientos llevados a cabo en línea que son más efectivos en mantener involucrado al usuario y reducir la sintomatología de trastorno de la conducta alimentaria (TCA). La presente revisión y meta‐análisis pretende determinar qué componentes de las intervenciones de autoayuda para TCA basadas en la web, están asociadas con menor deserción y resultados terapéuticos mejorados. Método: Una revisión sistemática de las bases de datos electrónicas (PsycINFO, Medline, Web of Science, Scopus) fueron revisadas buscando estudios de intervenciones para TCAs basadas en la web y se realizó un meta‐análisis de los estudios finalmente incluidos. Cada intervención fue codificada en cuatro dimensiones, incluyendo los canales multimedia (por ejemplo, texto, audio, videos), grado de interacción con el usuario (por ejemplo, auto monitoreo en línea, ejercicios de habilidades), nivel de retroalimentación automatizada (por ejemplo, recordatorios, retroalimentación personalizada), y aparatos tecnológicos a través de los cuáles se accesó al programa (por ejemplo, teléfonos inteligentes, computadora). Resultados: Al final fueron incluidos 23 estudios. Los resultados de las meta‐regresiones indicaron que puntuaciones más elevadas en la subescala de multimedia estaba asociado con mayor mejoría de los síntomas de TCA en los grupos de tratamiento. Por lo contrario, un mayor grado de retroalimentación en el grupo de tratamiento fue asociado con una diferencia grupal en la psicopatología de TCA favoreciendo el grupo control. Otros componentes de la intervención no fueron asociados con resultados o abandonos de tratamiento. Discusión: Los resultados fueron discutidos en relación a las limitaciones de la escala utilizada para cuantificar las características de la intervención digital, así como la limitada diversidad y sofisticación tecnológica de las intervenciones digitales para TCA disponibles. Estos hallazgos indican la importancia de entender los componentes digitales que diferencían los programas terapéuticos en línea.